Lactation and mother-pup behaviour in the Mediterranean monk seal Monachus monachus: An unusual pattern for a phocid - Aguilar, A. (2007)
This paper presents baseline information on maternal behaviour and lactation in the Mediterranean monk seal, with particular focus on the age at which pups are weaned. The study was conducted in the western Saharan population, the only surviving colony of the species. The first moult finished at a mean pup age of 72.3±17 d (N=17) and, in contrast to other taxonomically-related phocids, this process was not associated with weaning. Lactation lasted a mean of 119.4 d (N=9; range: 103-149 d) in the pups that could be monitored until full weaning had taken place. This period almost doubles the maximum lactation length reported in other phocid species. During the first week after birth the mother-pup bond was well developed and mothers always remained with their pups. The time invested in nursing (17%, SD: ±36) and in mother-pup interactions (14%, SD: ±32) was higher during this period than afterwards (8%, SD: ±23 and 4%, SD: ±19, respectively). After the first week, nursing continued but mothers started to leave their pups in order to feed at sea. Weaning occurred gradually. Already since birth, pups were active and mobile, and swam frequently before moulting or weaning occurred. Fostering and milk stealing were common patterns of behaviour for both lactating females and pups. In 26.6% of the suckling episodes observed in mother-pup pairs of known identity, pups suckled from females other than their mothers. Some females nursed more than one pup, at least occasionally, and in some cases a pup was fostered long-term by an alien female. The Mediterranean monk seal exhibits maternal-care characteristics that are more like otarids than phocids. This observation contradicts previous proposals that a short lactation period is a phylogenetic characteristic of phocids. Several of the unusual maternal traits observed may be favoured by year-round access to abundant food supply, availability of breeding sites, and mild climatic conditions. This information should be taken into account when designing conservation strategies for the species and, very particularly, in the implementation of pup rehabilitation programmes.